2021
DOI: 10.1093/mnras/stab3107
|View full text |Cite
|
Sign up to set email alerts
|

Zodiacal exoplanets in time – XIII. Planet orbits and atmospheres in the V1298 Tau system, a keystone in studies of early planetary evolution

Abstract: Studies of planetary systems of stars in star-forming regions and young clusters open a window on the formative stages of planetary evolution. We obtained high-cadence high-resolution infrared spectroscopy of the solar-mass Taurus association-member V1298 Tau during a transit of its 10R⊕-size ‘b’ planet. We measured the systemic radial velocity (RV) and find that the kinematics of V1298 Tau suggest an affiliation with a ≳6 Myr-old subgroup. A comparison of V1298 Tau and the nearby, co-moving star 2M0405 with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…Our choice to focus on only single-star systems excludes some highly misaligned warm Jupiters in systems with more than one star (e.g., K2-290 c, Hjorth et al 2021;Kepler-420 b, Santerne et al 2014;and WASP-8 b Queloz et al 2010;Bourrier et al 2017). However, other warm Jupiters in binary or multistar systems have instead been observed in or near alignment (e.g., V1298 Tau b, Gaidos et al 2022 andJohnson et al 2022;and WASP-11 b, Mancini et al 2015). The set of obliquity constraints in binary star systems so far appears to be more heterogeneous than in the sample of single-star systems, and further measurements are required to delineate the dominant trends in this population.…”
Section: Population Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our choice to focus on only single-star systems excludes some highly misaligned warm Jupiters in systems with more than one star (e.g., K2-290 c, Hjorth et al 2021;Kepler-420 b, Santerne et al 2014;and WASP-8 b Queloz et al 2010;Bourrier et al 2017). However, other warm Jupiters in binary or multistar systems have instead been observed in or near alignment (e.g., V1298 Tau b, Gaidos et al 2022 andJohnson et al 2022;and WASP-11 b, Mancini et al 2015). The set of obliquity constraints in binary star systems so far appears to be more heterogeneous than in the sample of single-star systems, and further measurements are required to delineate the dominant trends in this population.…”
Section: Population Analysismentioning
confidence: 99%
“…However, other warm Jupiters in binary or multi-star systems have instead been observed in or near alignment (e.g. V1298 Tau b (Gaidos et al 2022;Johnson et al 2022) and WASP-11 b (Mancini et al 2015)). The set of obliquity constraints in binary star systems so far appears to be more heterogeneous than in the sample of single-star systems, and further measurements are required to delineate the dominant trends in this population.…”
Section: Population Analysismentioning
confidence: 99%
“…The other numbers refer to other works reporting additional measurements of λ or other system parameters. Note-All data were taken from TEPCat (Southworth 2011) or the following references: 1 (Hirano et al 2020a), 2 (Albrecht et al 2021), 3 (Martioli et al 2020), 4 (Palle et al 2020, 5 (Addison et al 2021), 6 (Christiansen et al 2017), 7 (Bourrier et al 2021, (Dalal et al 2019), 9 (Mann et al 2020), 10 (Dai et al 2020), 11 (Zhou et al 2018, 12 (Hjorth et al 2019a), 13 (Hjorth et al 2021, 14 (Wang et al 2018), 15 (Albrecht et al 2013), 16 (Campante et al 2016, 17 (Benomar et al 2014), 18 (Sanchis-Ojeda et al 2012, 19 , 20 (Huber et al 2013), 21 (Hirano et al 2012), 22 (Newton et al 2021, 23 (Zhou et al 2021), 24 (Wirth et al 2021), 25 (Hirano et al 2020b), 26 (David et al 2019b), 27 (Johnson et al 2021), 28 (Biddle et al 2014), 29 (Gaidos et al 2021), 30 (Feinstein et al 2021), 31 (Sanchis-Ojeda et al 2015, 32 (Wang et al 2021b), 33 (Hébrard et al 2020) 3.1.12. Interlude: Mutual orbital inclinations Most of the available RM data are for stars with closeorbiting giant planets.…”
Section: Obliquity and Eccentricitymentioning
confidence: 99%
“…Zhang et al (2022a) reported escaping He I for the 500 Myr old mini-Neptune HD 73583 b, showing an excess 0.68% absorption for the He I 10830 Å line. Tentative detections of atmospheric escape have been reported for planets in the V1298 Tau system in Ca II, H-α (Feinstein et al 2021), and He I (Gaidos et al 2022).…”
Section: Introductionmentioning
confidence: 99%